Mappanonno Ritual among Bugis Muslims: Between Gratitude, Ancestral Tradition, and Religious Belief - Muhammad Zuhri Abu Nawas; Sarliana Sarliana; Muhammad Ashabul Kahfi (Postgraduate Program of the State Islamic Institute of Palopo, 2024)
This study examines the Mappanonno ritual among the Bugis Muslim community in Bone, Indonesia, with a focus on understanding its ritual process, cultural meanings, and religious dimensions. Specifically, this study explores how Mappanonno reflects expressions of gratitude, ancestral tradition, and religious belief within the lived experiences of the local community. This study employed a qualitative field research design using a phenomenological approach. The research was conducted in Lea Village, Tellu Siattinge District, Bone Regency, South Sulawesi. Data were collected through observation, in-depth interviews, and documentation involving traditional leaders, religious figures, community elders, and local residents. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that Mappanonno consists of four main stages: preparation of ritual offerings, communal prayer and Qur’anic recitation, symbolic offering at the river, and communal gathering. The ritual carries multidimensional meanings for the community, functioning as an expression of gratitude to Allah, a means of preserving ancestral heritage, and a spiritual practice associated with protection from misfortune (pattola bala). The study also finds that Islamic elements are strongly embedded in the ritual through collective prayers and the recitation of selected Qur’anic chapters such as al-Fatihah, al-Ikhlas, al-Falaq, and an-Nas. This study concludes that Mappanonno represents a meaningful intersection of gratitude, ancestral tradition, and religious belief, reflecting the dynamic integration of Islam and local culture in Bugis Muslim society.